Does attractiveness win? On the gender-specific impact of attractiveness on athletic performance in tennis - Linn-Brit Bakkenbüll (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2016)
This study examines whether there are gender-specific differences in regard to physical attractiveness of professional tennis players and their performance. For this purpose, the top 100 male and female tennis players of the tennis world ranking in 2014 are examined. Athletic performance is measured by prize money earned for single seasons as well as for the whole career. Different OLS-regressions reveal a significantly positive relationship between physical attractiveness and athletic performance. However, this result holds for female tennis players only. For male tennis players, the impact is insignificant. – – Diese Studie untersucht, ob ein geschlechtsspezifischer Zusammenhang zwischen der Attraktivität von professionellen Tennisspielern und ihrer sportlichen Leistung besteht. Dazu werden die Top 100 Tennisspielerinnen und -spieler der jeweiligen Weltrangliste im Jahr 2014 untersucht. Die Leistung wird über gewonnene Preisgelder für einzelne Saisons sowie für die gesamte Karriere gemessen. Verschiedene OLS-Regressionen zeigen einen signifikant positiven Zusammenhang zwischen der physischen Attraktivität und der sportlichen Leistung. Dieser Zusammenhang besteht allerdings nur für Frauen. Für männliche Tennisspieler ist der Effekt insignifikant.
Keywords: J24; J31; J49; J71; L83; 650